Indigenous Aeta Magbukún self-identity, social-political structures, and self-determination at the local level in the Philippines - Balilla, V.; Anwar McHenry, Julia; McHenry, M.; Parkinson, R.; Banal, D. (Hindawi Publishing Corporation, 2013)
The Indigenous Aeta Magbukún maintain a primarily nomadic hunter-gatherer lifestyle in their forested ancestral lands. Through the continued encroachment of non-Indigenous populations, the Aeta Magbukún persist at a critical level. Finding it increasingly difficult to sustain their traditional livelihoods, they must engage in informal commerce to procure sufficient food throughout the year. This work explores the basis of self-identity, traditional kinship ties, evolution of sociopolitical organisation, and the developing political options that sustain the small and vulnerable Indigenous population. Despite recent tentative sociopolitical developments, securing cultural protection requires greater effort in developing political communication and representation at a local and national level. In doing so, the Aeta Magbukún can meet their basic needs, secure traditional cultural knowledge, and are able to influence their own development during a time of relatively rapid acculturation within the mainstream Philippine societal complex.